Peningkatan Kualitas Produksi Home Industri Ria Mandiri Melalui Pengembangan Model Roster dan Paving Block - Nurmiah; Umar, Indriani; Muslimin, Eviliona; Urfan (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2024)
Home industry RIA MANDIRI is an independent business unit that started its business in 2014 in the Marisa sub-district, Sipatana village, which is engaged in the production of building materials with specifications for Bricks, Roster and Paving, which was initially started to employ teenagers and local fathers. Production problems that occur due to the absence of loster and paving mold forms which are characteristic of RIA MANDIRI's home industry due to a lack of knowledge of modifications in paving and loster design models. the texture of the results is not appropriate, the low level of understanding of members in the group in producing bricks, paving and losters that comply with building material structure standards, and the absence of skilled workers who have special competence in building materials so that the smooth texture and design has its own uniqueness. The aim of PKM This is to increase the development of a creative and independent industry in terms of empowering a productive industry, Implementation Methods in the field of production holding workshops, mentoring, equipment maintenance, the implementation of the Ria Mandiri Home Industry starts with improving the Production Process, updating the production system tools. The servant believes this will be able to changing the production value and marketing volume of the Ria Mandiri Home Industry, measuring the level of progress by carrying out scheduled evaluations and monitoring, providing assistance in the form of laptops for model design tools and paving brick production workshops that comply with construction standards, assisting in the process of checking sand raw materials, providing skills guidance use and maintenance of tools. The result of the application of this service science and technology is an increase in understanding, changes and skills of partners in the brick paving process which is more productive, innovative and also able to have unique model results. . Success measurement was 78%. The next field of activity is in the field of green production